(3Gdbhd GdhLjR aj CMcGe GdcJGH GdYRjRs - (3CMeO Hf jhSa Hf YHO GdOGje GdMdHj, CHh GdYHGS, TgGH GdOjf GdeYQha HGdSejf,J (B756 (3g` s
(3ChdgG (B:s
(3Chdg eHJhQ(B: (3Gh MVQ CMOce GdehJ dgOA MQ GdGde hGNJda GdfGS s
(3BNQgG (B:s
(3adeG PcQhg fYe GOGA GdWdGb GdhGMO jOd Ydi ESbGW Gdedc hGdMeO ddg hMOg MSHfG Gddg hfYe Gdhcjd , GfJgi GdLRA GdKGfi ef Gdbhd GdhGMOi s
(3GdfSNI HgG MhGTs
(3HgG JedjcGJs
(3HgG fXGe GdJYbjHIs
(3ef GdLRA GdKGfi Edi GdJGSY ai KeGfjI eLdOGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B274 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B211s
Keywords: (3GdJaSjQ hYdhe GdbQBfs